ROLE OF SELF-ESTEEM IN SECOND LANGUAGE ORAL AND WRITTEN PERFORMANCE - FOTIMAKHON ABDUMALIKOVA (International Journal of Innovations in Engineering Research and Technology, 2021)
The current study attempts to examine the effect of the level of learners self-esteem in second language oral and written production. To be more precise, it investigates how do low and high level of self-esteem influence on the productive skills of learners as a personal factor and to raise teachers awareness about the importance of self-esteem in the success of learners speaking skill. This research work is based on the hypothesis if learners have a high level of self-esteem, they will be able to trust their own abilities which in turn will increase their level of oral skill production. The most suitable method to this study will be comparative analytical method in order to demonstrate differences between low self-esteem and high self-esteem in oral and written language production before and after feedback by the teacher. This study mainly based on questionnaire, two different types of class project results. The analysis of the questionnaires results revealed that both teachers and learners strongly support the importance of self-esteem as an affective factor in improving the oral production performance.